IGRZYSKA OLIMPIJSKIE W RIO DE JANEIRO W MEMACH INTERNETOWYCH - Kępa-Figura, Danuta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents an image of the Games and an image of other pieces of reality contained in internet memes about the XXXI Summer Olympics. The multimodal nature of the analyzed messages was taken into account and the analyzes carried out were included in the genological research and the study of the media image of the world. The ways of entering individual meanings are described. The correctness that governs the way in which the world is spoken in memes is indicated, such as anthropocentrism, polishcentrism and emotioncentrism, and consequently the cognitive properties of the genre pattern of the internet memes. The internet memes was characterized as a species used to evaluate the world based on distance.